\(\left(x+7\right)\left(x-9\right)=0\)
<=> \(\hept{\begin{cases}x+7=0\\x-9=0\end{cases}}\)
<=> \(\hept{\begin{cases}x=-7\\x=9\end{cases}}\)
\(x+7\left(x-9\right)< 0\)
<=> \(x+7x-63< 0\)
<=> \(8x< 63\)
<=> \(x< \frac{63}{8}\)
học tốt
Tìm x :
( x + 7 ) . ( x - 9 ) = 0
<=> x + 7 = 0 hoặc x - 9 = 0
<=> x = 0 - 7 hoặc x = 0 + 9
<=> x = -7 hoặc x = 9
Vậy x € { -7 ; 9 }
( x + 7 ) . ( x - 9 ) < 0
<=> x + 7 và x - 9 khác dấu
<=> TH1 :
\(\hept{\begin{cases}x+7>0\\x-9< 0\end{cases}\Leftrightarrow\hept{\begin{cases}x>-7\\x< 9\end{cases}}}\Leftrightarrow-7< x< 9\)
TH2 :
\(\hept{\begin{cases}x+7< 0\\x-9>0\end{cases}\Leftrightarrow\hept{\begin{cases}x< -7\\x>9\end{cases}}}\) ( vô lí )
Vậy với -7 < x < 9 thì ( x +7 ) . ( x - 9 ) < 0
(x + 7)(x - 9) = 0
=> x + 7 = 0 hoặc x - 9 = 0
=> x = - 7 hoặc x = 9
vậy_
\(\left(x+7\right).\left(x-9\right)=0\Leftrightarrow\orbr{\begin{cases}x+7=0\\x-9=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-7\\x=9\end{cases}}}\)
Vậy : \(x=-7\)hoặc \(x=9\)
________
\(x+7.\left(x-9\right)< 0\)
Th1 : \(\hept{\begin{cases}x+7>0\\x-9< 0\end{cases}\Leftrightarrow\hept{\begin{cases}x>-7\\x< 9\end{cases}}}\Leftrightarrow-7< x< 9\)
Th2 : \(\hept{\begin{cases}x+7< 0\\x-9>0\end{cases}\Leftrightarrow\hept{\begin{cases}x< -7\\x>9\end{cases}\Leftrightarrow}x\varepsilon\varnothing}\)
Vậy : \(-7< x< 9\)